Stereoisomer effect on ferroelectric nematics: stabilization and phase behavior diversification. Issue 22 (25th May 2022) - Zhou, Junchen; Xia, Runli; Huang, Mingjun; Aya, Satoshi
Abstract : Stabilization and diversification of phase behaviors in ferroelectric nematics driven by a stereoisomer effect are observed, which in turn modulates the viscoelastic and ferroelectric properties. Abstract : The ferroelectric nematic state is an emerging liquid crystalline state, combining fluidity and ferroelectricity. The incidence of such a unique state necessitates special requirements on molecular geometry and physicochemical parameters. However, how the specific molecular details modify the matter state remains unanswered. Here we focus on molecular geometry effects on the phase behaviour of ferroelectric nematics. We precisely synthesized pure stereoisomers for an important single molecular structure, DIO, which has been considered as a ferroelectric nematic material with a well-defined phase sequence. Unexpectedly, we discover that the material phase diagram has a strong dependence on the mixing ratio of the stereoisomers. The ferroelectric nematic phase can be stabilized at room temperature and evolve along a distinct pathway at suitable compositions. We also discuss how the viscoelasticity and polarity switching properties are changed by the mixing ratio. Our results provide accessibility to low-temperature stable NF materials and enrich the understanding of the structure–property relationships in NF mesophases.